Penerapan Media Matras Bidang Miring untuk Meningkatkan Hasil Belajar Guling Depan dan Guling Belakang Kelas X-10 SMAN 1 Gedangan Sidoarjo - Mohammad Rozikin; Sasminta Christina Yuli Hartati; Supriyanto Supriyanto (BADAN PENERBIT STIEPARI PRESS, 2024)
Media is an aid that can help teachers in facilitating students especially in the learning process. The application of media in the learning process must also be adjusted to the purpose and type of media used so that the learning process can run optimally. The problem of in this study is the students feel fear when practicing front roll and back roll. This fear can be an obstacle for students in doing the front roll and back roll movement optimally. In addition, there is also a lack of understanding of the students’ skills of front roll and back roll as well as the residual fear of doing the movement even though they are already based on a mat. Therefore, it is necessary to modify the facilities by using inclined plane mat media as a modification medium that can be an alternative in floor gymnastics materials in PJOK subjects. The purpose of this study is to find out how much improvement after being given a modification of the inclined plane mat media on the results of learning front roll and back roll in SMAN 1 Gedangan students. This study uses Class Action Research (CAR), which is a research methodology that carries out actions in two stages: Cycle I and Cycle II. The four main phases of PT implementation are action, planning, observation, and reflection. Sampling was carried out by purposive sampling to choose class X-10 SMAN 1 Gedangan which totaled 36 students as a research sample. To obtain the needed information, data collection techniques use attitude, knowledge, skill and observation tests. The data collected in each cycle is analyzed using descriptive analysis in the percentage method. After data collection, the results were obtained that there was an increase in the results of learning the front roll and back roll in the affective, cognitive and psychomotor domains of students. This can be seen in the increase of percentage obtained from cycle I to cycle II, which is 3% in the affective domain, 2% in the cognitive domain and 3% in the psychomotor domain. This is also proven by the results of learning the affective domain from cycle I to cycle Il as many as 6 students (16%). Meanwhile, the incompleteness caused an incomplete decrease of 6 students (16%). Therefore, in the results of learning the cognitive domain, from cycle I to cycle II completed as many as 18 students (50%).While, the incompleteness caused an incomplete decrease of 18 students (50%). Also, in the results of learning the affective domain from cycle I to cycle II completed as many as 9 students (25%). However, the incompleteness there was an incomplete decrease of 9 students (25%).